Chronic Spontaneous Urticaria: Clinical Profile, Autologous Serum Skin Test Positivity and Associated Impairment in Quality of Life in Nepalese Patients - Paudel, S.; Parajuli, N.; Sharma, R.; Parajuli, S. (Kathmandu University Medical Journal, 2022)
Background Chronic Spontaneous Urticaria is considered to be an autoimmune phenomenon in half of the total cases. Autologous serum skin test is a simple screening test for the presence of auto-antibodies in chronic urticaria. Significant impairment in quality of life have been observed in autologous serum skin test positive cases. There are limited literatures on chronic spontaneous urticaria, autologous serum skin test and associated Dermatology Life Quality Index in Nepal till date. Objective To find the proportion of autologous serum skin test positive cases in chronic urticaria and impairment in quality of life in such patients. Method This was a retrospective review of outpatient records of patients diagnosed with chronic spontaneous urticaria, from January 2018 to December 2019, from a tertiary care hospital in Kathmandu, Nepal. Details of the patients, autologous serum skin test and dermatology life quality index scores were analyzed and presented. Result Among the total 114 cases positive autologous serum skin test was seen in 48.2% of cases. The mean total Dermatology Life Quality Index score was 8.06±6.64. A significantly higher quality of life impairment was observed in in patients with positive autologous serum skin test as compared to the negative ones. The odds of finding a positive autologous serum skin test in patients with angioedema was 2.1, however the difference was not statistically significant. Conclusion Chronic spontaneous urticaria was more common in females as compared to males. A positive autologous serum skin test was present in half of the patients which was in turn associated with a greater impairment of quality of life.